2020
DOI: 10.1002/admi.201902075
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorescence Probe for Metal Ions Based on Black Phosphorus Quantum Dots

Abstract: spectroscopy (ICP-AES), and surface plasmon resonance sensing. [4][5][6] Although these methods have high detection performances, the complicated preprocessing process and the excessive cost limit their range of use and the detection rate. On the other hand, with the advancement of fluorescence technology, fluorescence detection techniques for metal ions by monitoring the fluorescence enhancement, quenching, or shifting of peak positions have attracted great interests. This type of method has advantages of str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…A similar effect can be achieved by the incorporation of different surface functional groups or element doping. [206,211] Xu et al demonstrated a more practical Cu 2+ fluorescence probe based on BP QDs, which can be used in both aqueous and organic solutions. [211]…”
Section: Heavy Metal Ion Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar effect can be achieved by the incorporation of different surface functional groups or element doping. [206,211] Xu et al demonstrated a more practical Cu 2+ fluorescence probe based on BP QDs, which can be used in both aqueous and organic solutions. [211]…”
Section: Heavy Metal Ion Detectionmentioning
confidence: 99%
“…[206,211] Xu et al demonstrated a more practical Cu 2+ fluorescence probe based on BP QDs, which can be used in both aqueous and organic solutions. [211]…”
Section: Heavy Metal Ion Detectionmentioning
confidence: 99%
“…A series of detection methods have been developed to detect silver ions, such as atomic absorption spectroscopy, inductively coupled plasma–mass spectroscopy, and ion-selective electrodes. , However, these methods mentioned above all require expensive equipment or complex technology. On this basis, fluorescent probes have become a popular method due to their high sensitivity, rapidity, simple operation, common instruments, and suitability for biological systems. In the past years, some fluorescent probes for detecting silver ions have been developed, but the following defects are still not solved. First, some currently reported methods utilize the “silent ion” of silver ions to quench their fluorescence, which is not conducive to high signal output. , Second, the proposed probes only show moderate fluorescence changes, small response range to silver ion concentration, so the sensitivity of these probes is usually not enough to detect low concentrations of silver ions in water samples. , Finally, the probes reported in the literature are difficult to distinguish Ag + from other metal ions (such as Au 3+ ). , Therefore, it is an urgent need to develop a novel fluorescent probe with high sensitivity and selectivity in real samples. …”
Section: Introductionmentioning
confidence: 99%
“…Atomic absorption spectroscopy, inductively coupled plasma mass spectroscopy (ICP-MS), X-Ray uorescence have been reported in the literature to be used for the detection of heavy metal ions in environmental samples. But however their use has been limited because of their high cost and complicated instrumentation [9,10,11,13,14].…”
Section: Introductionmentioning
confidence: 99%